قاعدة القحف وعلاقتها باتجاه دوران الفكين لدى البالغين (دراسة بواسطة التصوير الطبقي المحوري المخروطي( - جحجاح يزن; خونده محمد (Latakia University Journal -Medical Sciences Series, 2016)
Facial structures, as well as their functions and correlations, have been extensively studied to expand the knowledge of craniofacial growth and development and to optimize growth predictions and proper indications of orthodontic and surgical treatments. The cranial base forms the boundaries of the craniofacial complex . The nasomaxillary complex is related to the anterior cranial base, whereas the mandible is related to its posterior portion. Therefore, the shape of the cranial base is an important factor in establishing the position of the maxilla and mandible. Aim: to investigate the relationship of cranial base with jaws rotation in adult orthodontically non-treated subjects using Cone-Beam Computed Tomography (CBCT) scan. Materials and methods: 27 Caucasian adult patients with no prior orthodontics treatment were selected (16 males, 11 females) .Cephalometric measurements determining type of jaw rotation were performed according to Björk’s analysis. Pearson’s Correlation Coefficient was calculated to investigate the relationship between the CBCT cranial base measurements and Cephalometric measurements determining type of jaw rotation . Results: This study reveal vary correlation between CBCT measurements of cranial base’s dimensions and jaws rotation. Conclusions: There is no relationship between the cranial base morphology and Jaws rotation in adult orthodontically non-treated subjects. درست البنى الوجهية و علاقتها مع البنى المجاورة بشكل كبير بهدف الحصول على معلومات واسعة عن عملية النمو والتطور التي تحدث في منطقة المركب القحفي الوجهي بحيث يمكننا من التنبؤ باتجاه النمو والتداخلات العلاجية الجراحية والتقويمية التي يمكن إجراؤها عند الحاجة .هذا ينتمي المركب الأنفي الفكي العلوي إلى قاعدة القحف الأمامية في حين يرتبط الفك السفلي مع الجزء الخلفي من قاعدة القحف , لذلك تعتبر دراسة قاعدة القحف والتغيرات الشكلية التي تصيبها عاملا هاما في تحديد موقع كل من الفكين العلوي والسفلي. هدف البحث : تحري وجود علاقة بين قاعدة القحف وبين ودوران الفكين لدى مرضى بالغين غير معالجين تقويميا باستخدام التصوير الطبقي المحوري المخروطي . مواد وطرق البحث : اعتمادا على نتائج الدراسة الشعاعيىة ,بلغ عدد أفراد العينة 27 بالغاً (16 ذكور،11 أنثى) ممن لم يخضعوا لمعالجة تقويمية سابقة حيث تم انتقاؤهم من مرضى كانوا تلقائياً بصدد إجراء تصوير طبقي محوري مخروطي لأسباب لا تتعلق بمشاكل تقويمية ، تم إجراء دراسة سيفالومترية لتحديد اتجاه دوران الفكين وفق تحليل بيورك ، ومن ثم تحليل معامل ارتباط بيرسون لدراسة العلاقة بين قياسات قاعدة القحف المجراة على صور الطبقي المحوري المخروطي مع القياسات السيفالومترية المحددة لاتجاه دوران الفكين . النتائج : أظهرت الدراسة وجود تنوع في الارتباط بين قياسات قاعدة القحف المجراة على صور الطبقي المحوري المخروطي مع القياسات الخاصة بنموذج دوران الفكين وفق تحليل بيورك. الخلاصة : لم يلاحظ وجود علاقة بين مورفولوجيا قاعدة القحف مع نموذج دوران الفكين لدى المرضى البالغين الغير خاضعين لمعالجة تقويمية .